2010
DOI: 10.1111/j.1365-2133.2010.09640.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of androgenetic alopecia in China: a community-based study in six cities

Abstract: The prevalence of AGA in Chinese men and women was lower than in Caucasians and similar to that in Koreans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
175
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(195 citation statements)
references
References 19 publications
(49 reference statements)
13
175
6
1
Order By: Relevance
“…In the present study Grade IV was the most common grade of alopecia and grade VI was least common which was comparable to study done by Wang et al 26 in which grade IV was the commonest type. In a population based study by Dr DS Krupa Shankar 22 the most common grade was grade II (27.27%) followed by grade I (22.12%) and grade III (21.78%).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the present study Grade IV was the most common grade of alopecia and grade VI was least common which was comparable to study done by Wang et al 26 in which grade IV was the commonest type. In a population based study by Dr DS Krupa Shankar 22 the most common grade was grade II (27.27%) followed by grade I (22.12%) and grade III (21.78%).…”
Section: Discussionsupporting
confidence: 79%
“…In a study done in Iran MHEC containing 3 hair growth promoters(minoxidil 12.5%, azelaic acid 5%, betamethasone-17-valerate 0.025%) seemed to be effective in hair loss treatment, more potent than minoxidil 5% alone , without intolerable adverse effects and was to be considerd for AGA patients who do not respond well to minoxidil alone 26 .…”
Section: Group 2: Combination Of Topicalmentioning
confidence: 99%
“…It is evident from studies that hair loss patterns have regional differences [21,22] . The differences have also been noted among European and Asian population [11,16] .…”
Section: Discussionmentioning
confidence: 99%
“…The differences have also been noted among European and Asian population [11,16] . A Chinese study showed different ratios in various cities of china [21] . Among various classification system of hair loss, the reliability of Norwood systems vs. basic and specific patterns (BASP) have been compared which concluded that BASP was better than Norwood's classification [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of its prevalence in women have varied widely, though recent studies claim that 16% of women aged less than 50 years are affected, increasing to a proportion of 30-40% of women aged 70 years and over [21]. It is assumed that the genetically predisposed hair follicles are the target for androgen-stimulated hair follicle miniaturization, leading to gradual replacement of large, pigmented hairs (terminal hairs) by barely visible, depigmented hairs (vellus hairs) in affected areas with consequent loss of hair density.…”
Section: Hair Loss In Females Female Pattern Hair Lossmentioning
confidence: 99%